Successional changes of phytodiversity on a short rotation coppice plantation in Oberschwaben, Germany - Birmele, Janine; Kopp, Gabriele; Brodbeck, Frank; Konold, Werner; Sauter, Udo H. (Frontiers in Plant Science, 2015)
To allow for information on successional changes in phytodiversity over time and space, as well as information on differences between clones and treatments, phytodiversity was monitored on a poplar short rotation coppice plantation in Oberschwaben, Southwest Germany, in four consecutive years. The investigated plantation was divided into two core areas, one planted with poplar clone Max4, the other with Monviso; each core area was divided into two blocks with alternating treatments: i) irrigation and fertilization; ii) irrigation; and iii) no treatment. All vascular plant species of the ground vegetation were recorded in 72 permanent sampling plots of 25 m² each during vegetation periods using the Braun-Blanquet scale. Results showed that total number of species increased in first two years and declined after harvest of the SRC-trees. Total vegetation cover decreased during the four years of study. Especially for the two clones there was an opposed trend: grass layer had a high cover on Monviso plots, but low cover on Max4 plots; herb layer the very reverse. However, there was no significant difference between the three treatments compared within each year. Perennial species were dominating over all years, as well as light-demanding species, but their proportion decreased steadily. Our results confirm the conclusion of previous studies which indicate that plant community succession takes place in ground vegetation of SRC and imply that species composition is age-dependent. The selection of clones for SRC can influence ground vegetation; some floristic changes for example caused by different treatments may be visible only when monitored over a longer period of time.